EKONOMETRYCZNE MODELE PRZESTĘPCZOŚCI - Sztaudynger, J. Jacek; Sztaudynger, Marcin (Wydział Prawa i Administracji UAM, 2003)
This paper analyzes economic factors of criminal activity, some prominence is also given to certain legal and sociological aspects. The presented results to a large extent conform to the model created by P. Fajzynbler, D. Lederman and H. Loayza. The phenomenon of criminal activity can be precisely described in a formalized, model-like manner. Empirical verification of the model indicates that criminal activity is to a large extent motivated by economic factors and can be explained in terms of decisions based on the analysis of costs and profits to be derived from criminal actions. Therefore, the phenomenon of criminal activity is not merely an outcome of low moral standards of individual persons from the dregs of the society. This statement has been verified by the data not only from Poland but also other countries. However, it is not to provide a ready-made excuse for criminal activity but rather a hint for the national policy makers showing how to eliminate the broadly understood “chances” The verification of the model displays to what extent criminal activity can be reduced while improving the law enforcement rate. The research also indicates that the focus on economic growth, bridging the income gap, decreasing alcohol consumption and reduction of unemployment can to a large extent counteract the persistence of criminal activity. It should be not that in Poland criminal activity is tightly interconnected with unemployment. One percentage point higher in the unemployment rate has caused the increase in the criminal activity rate by as much as 2.8%. This figure serves as yet another case for fighting unemployment. The level of income earned by the population can impact the criminal activity rate either negatively or positively. By 1900 the beneficial negative impact prevailed, however after 1990 the income rate has been stimulating criminal activity, which goes on to prove that system transformation has come at a price.
ECONOMETRIC MODELS OF CRIMINAL ACTIVITY